Hemogram reference values for Lisbon metropolitan area population. - Azevedo, Ana Paula (2010)
The haemogram is, probably, one of the most requested analysis for laboratorial evaluation not only for ill patients but also in periodic evaluation of healthy subjects, allowing us to foil the presence of eventual illness, since there is an enormous variety of pathologies that can induce haemogram changes. The haematological parameters of healthy subjects are influenced by numerous factors. The ideal would be each laboratory should determine and establish his own reference values for each parameter, having in account all the variables. Since the available data for haematological parameters in the Portuguese population is very insufficient, it becomes necessary to report to exterior data based in populations with different characteristics from ours, which makes reference values' reliability questionable. To overcome this problem, we felt the necessity to evaluate our own population (healthy adults from metropolitan Lisbon area) concerning haemogram reference values, comparing the obtained results with those from the bibliography. We analyzed 363 blood samples from blood-donors that fulfilled the previously established protocol. The samples were collected before blood donation and the haemograms were done on the same day. We proceeded to the informatic registration of haemogram results, to the gathering of important data, to the characterization of the target population and to the statistical analysis of the obtained results. The sample population was globally analyzed and several groups were compared, according to sex, age group and possible history of smoking habits. Although we did not find in the bibliography data concerning the quantitative analysis of similar groups compared to ours, globally we concluded that the obtained results are similar to those described by other authors, both in qualitative and quantitative terms. The obtained results can only be of reference for this population and created subgroups. The definition of reference values for the Portuguese population requires the study of a much larger sample, due to the populational diversity that characterizes our country.